Perkembangan Sejarah dan Isu-Isu Terkini dalam Sastra Bandingan - Dipa Nugraha (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This article aims to describe the historical development of comparative literature and its current issues. Comparative literature is a mandatory course in the Indonesian language and literature study program in most Indonesian universities. There are at least six books used as common references in teaching comparative literature in Indonesia. However, these books have not covered recent development in comparative literature, especially the emergence of Chinese school and some new directions within comparative literature. This literature review article collects references from selective authoritative sources on the internet to describe the historical development of comparative literature and its current issues. This article shows that the expansions in comparative literature are intricate with deconstruction and reconstruction of world literature, dialogue and the meeting between West and East, and the presence of the digital age. From the dialogue on world literature and West meeting East vice versa, the Chinese school has its foundation, whilst the presence of the digital age makes comparative literature have new things to explore and work on the usage of the different medium in an umbrella term, intermediality.